Science Process Skills and Attitudes toward Science of Lower Secondary Students of Merbau Island: A Preliminary Study on the Development of MaritimeBased Contextual Science Learning Media - Zulirfan Zulirfan; Muhammad Rahmad; Yennita Yennita; Nina Kurnia; Muhammad Sofyan Hadi (Journal of Educational Sciences, 2018)
Science learning outcomes such as science process skills and attitudes toward science are still important issues in science education. In this study the researchers tried to get a picture of the students' learning outcomes to get input on the learning process of science in the coastal area. As an initial study of the development of maritime-based contextual science learning media, the purpose of this research is to know the extent of science process skill level, attitude toward science, and academic achievement of students in coastal area. There were 114 students of the 8th grade of four lower secondary schools in Merbau Island participated as respondents in this study. Instruments used in data collection are science process skills tests and attitude toward science questionnaires for lower secondary school students. The results showed that 8th grade lower secondary school students in Merbau Island had high attitude toward science. On the contrary, the science process skills and academic achievement of their science are relatively low.